Histopathological Features of Lymph Nodes of Tuberculous Lymphadenitis Patients: Experience of 50 cases in Bangladesh (Bangladesh Journal of Infectious Diseases, 2017)
Background: Tuberculous lymphadenitis is common manifestation of extra-pulmonary tuberculosis in Bangladesh. Objective: The purpose of the present study was to see the histopathological features of tuberculous lymphadenitis patients. Methodology: This cross sectional study was done at the Department of Pathology at Banghabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2009 to March 2011 for a period of nearly two years. All the patients irrespective of age and sex with the clinical features suggestive of tuberculous lymphadenitis and later on proved to be the same histologically were selected for the study purposively. Relevant information was recorded in a prescribed data sheet and histomorphological findings were recorded accordingly. In cases where fresh specimen was available, caseous portion of lymph node was sent for culture. FiteFaraco staining was also done on lymph node sections in all cases. Result: A total number of 50 tuberculous lymphadenitis patients were recruited for this study of which well formed granuloma was detected in 34(68.0%) cases followed by ill defined and combination of well and ill defined which were 8(16.0%) cases in each. Among 34 well defined cases coalescing and discrete were found in 6(17.6%) cases in each. However, both types were found in 22(64.7%) cases.Conclusion: In conclusion well formed granuloma is most commonly found in tuberculous lymphadenitis with combined variety of coalescing and discrete histopathologic featuresBangladesh Journal of Infectious Diseases 2016;3(2):40-42